Lyapunov stability theory for dynamic systems on time scales. (1992) - Kaymakçalan, Billur
Abstract : By use of the necessary calculus and the fundamental existence theory for dynamic systems on time scales, in this paper, we develop Lyapunov's second method in the framework of general comparison principle so that one can cover and include several stability results for both types of equations at the same time.